Make your own rules a renegade guide to unconventional success - Rogers, Wayne 1933-2015; Young, Josh (American Management Association, 2011)
In today's business environment--one where the traditional career path isn't as readily available as it once was; the economy and the banking system are volatile; and government regulation makes it increasingly difficult for entrepreneurs and new business owners to get their ideas off the ground--more and more people are seeking an alternate path to success. It's the kind of world where learning to be creative, challenging convention, and seizing unexpected opportunities are not only liberating but can also make the difference in whether or not you achieve personal and economic freedom. Wayne Rogers should know. The former star of the classic television series M A S H is a highly successful entrepreneur who, since graduating from Princeton University, has applied his own iconoclastic vision to a wide range of businesses including a vineyard, a famous bridal boutique, a chain of convenience stores, the worlds of banking and real estate, a restaurant, a film distribution company, and more. Rogers has made a name for himself in countless businesses where the only constant was that he lacked the traditional background and experience--proving time and time again that the secret to making it lies in tapping into your own creative viewpoint. In Make Your Own Rules, Rogers shares the keys to his success over the past four decades, revealing that you don't have to be "against the system" in order to succeed; you just have to avoid becoming a cog in a machine. Filled with insights and engaging stories, Make Your Own Rules encourages you to stop asking "Why?" and start saying "Why not?" when it comes to your career and business. Whether you're wrestling with how to transition from one career to another, seeking opportunities you can't yet see, or looking for a bold new way to start or revitalize your own business, Make Your Own Rules provides you with realistic strategies that will enable you to achieve phenomenal success in any area ... just by being yourself.
Includes index. - Description based on print version record and CIP data provided by publisher
Keywords: Rogers, Wayne -- 1933-2015; Businessmen -- Biography -- United States; Success in business; Rogers, Wayne / 1933-; Rogers, Wayne; 1933-2015; Hommes d'affaires; États-Unis; Biographies; Succès dans les affaires; BIOGRAPHY & AUTOBIOGRAPHY; General; BUSINESS & ECONOMICS; Careers; General; Businessmen; United States; Biographies